Description of a new species of the genus Hyalessa China (Hemiptera: Cicadidae: Sonatini) from Yunnan, China, with a key to the species of Hyalessa and a calling song analysis for two Hyalessa species - Puissant, Stéphane; Lee, Young June (Zootaxa, 2016)
A new species, Hyalessa scutata sp. nov., is described from Yunnan, China. This species is similar to Hyalessa fuscata (Distant, 1905) but is distinguished by the larger male opercula and the evenly narrow uncal lobe. Hyalessa ella (Lei & Chou, 1997) syn. nov. is synonymized with Hyalessa stratoria (Distant, 1905). A detailed sound analysis of the calling songs of Hyalessa fuscata (Distant, 1905) and Hyalessa maculaticollis (De Motschulsky, 1866) is provided. A key to the species of Hyalessa China, 1925 is also provided. A discussion is conducted for the first time about the presence of potential hybrids between H. maculaticollis and H. fuscata within Tsushima Island situated in the Korea Strait.